The basis of membrane stabilized effect of kopaxon in multiple sclerosis - L. I. Reikhert; O. A. Kicherova; A. A. Sokolova; Zsh. I. Molchanova (Бюллетень сибирской медицины)
We have studied the influence of kopaxon on the structure of lipid phase of cellular membranes of red corpuscles, the condition of process of peroxide lipids oxidation and the system of antioxidative defence of 58 people with remittent form of multiple sclerosis. On the grounds of analysis of dynamics of laboratory index, membrane stabilized effect of this preparation was proved.